Neutrophil Migratory Patterns: Implications for Cardiovascular Disease - Dahdah, Albert; Johnson, Jillian; Gopalkrishna, Sreejit; Jaggers, Robert M.; Webb, Darren; Murphy, Andrew J.; Hanssen, Nordin M. J.; Hanaoka, Beatriz Y.; Nagareddy, Prabhakara R. (Frontiers in Cell and Developmental Biology, 2022)
The body’s inflammatory response involves a series of processes that are necessary for the immune system to mitigate threats from invading pathogens. Leukocyte migration is a crucial process in both homeostatic and inflammatory states. The mechanisms involved in immune cell recruitment to the site of inflammation are numerous and require several cascades and cues of activation. Immune cells have multiple origins, and can be recruited from primary and secondary lymphoid, as well as reservoir organs within the body to generate an immune response to certain stimuli. However, no matter the origin, an important aspect of any inflammatory response is the web of networks that facilitates immune cell trafficking. The vasculature is an important organ for this trafficking, especially during an inflammatory response, mainly because it allows cells to migrate towards the source of insult/injury and serves as a reservoir for leukocytes and granulocytes under steady state conditions. One of the most active and vital leukocytes in the immune system’s arsenal are neutrophils. Neutrophils exist under two forms in the vasculature: a marginated pool that is attached to the vessel walls, and a demarginated pool that freely circulates within the blood stream. In this review, we seek to present the current consensus on the mechanisms involved in leukocyte margination and demargination, with a focus on the role of neutrophil migration patterns during physio-pathological conditions, in particular diabetes and cardiovascular disease.